The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1080/03079459408418991
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal disorders in the fowl: A review

Abstract: SUMMARYSelection pressure for production traits in modern lines of poultry has placed increasing demands on skeletal integrity. Disruption of the normal process of skeletal growth and homeostasis results in bone diseases that are manifest throughout the modern poultry industry. Bone conditions in poultry can be grouped under three headings based on the age and type of fowls affected, and are indicative of the genetic and production stresses applied to the skeleton. In broilers during growth it is primarily pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
77
0
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(81 citation statements)
references
References 216 publications
(233 reference statements)
0
77
0
4
Order By: Relevance
“…It could also be proposed that reduced physical activity could have led to the reduced observed tendency to spill feed in modern commercial breeds, as was discussed in section 2. It makes sense to select for low physical activity, at least from an energy consumption perspective, if not for the associated animal welfare concerns (Thorp 1994;Craig and Muir 1998). It should be also noted that contrasting results were found in a study by Skinner-Noble et al (2003) where it was shown that birds selected for better feed conversion efficiency actually showed a small but significant increase in time spent standing and a decrease in resting behavior.…”
Section: Metabolic Activitymentioning
confidence: 99%
“…It could also be proposed that reduced physical activity could have led to the reduced observed tendency to spill feed in modern commercial breeds, as was discussed in section 2. It makes sense to select for low physical activity, at least from an energy consumption perspective, if not for the associated animal welfare concerns (Thorp 1994;Craig and Muir 1998). It should be also noted that contrasting results were found in a study by Skinner-Noble et al (2003) where it was shown that birds selected for better feed conversion efficiency actually showed a small but significant increase in time spent standing and a decrease in resting behavior.…”
Section: Metabolic Activitymentioning
confidence: 99%
“…Reduction in growth rate during the starting period has been shown to be effective in reducing the occurrence of leg problems (Classen, 1992;Thorp, 1994;Leterrier and Constantin, 1996 for review). Another method is to enhance motor activity, which is known to improve the musculoskeletal apparatus (Thorp and Duff, 1988) and thus reduce the occurrence of these abnormalities in both experimental (Reiter and Bessei, 1998;Reiter, 2004) and field conditions (Waldenstedt and Lansfors, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic selection has been used to reduce these diseases because susceptibility to leg problems differs between hybrids and heritability of such traits is relatively high (Kestin et al, 1992;Le Bihan-Duval et al, 1996 andKestin et al, 1999;Sanotra et al, 2003). However, there is still a need to identify suitable rearing methods to improve leg condition.Reduction in growth rate during the starting period has been shown to be effective in reducing the occurrence of leg problems (Classen, 1992;Thorp, 1994;Leterrier and Constantin, 1996 for review). Another method is to enhance motor activity, which is known to improve the musculoskeletal apparatus (Thorp and Duff, 1988) and thus reduce the occurrence of these abnormalities in both experimental (Reiter and Bessei, 1998;Reiter, 2004) and field conditions (Waldenstedt and Lansfors, 2003).…”
mentioning
confidence: 99%
“…The prevention and control of these disorders in birds depends on the advances in the understanding of the physiological mechanisms that govern normal skeletal growth and of the biology of avian skeletal disorders (16). Few investigations have studied the cartilage of birds with respect to the biochemical composition of its extracellular matrix.…”
Section: Introductionmentioning
confidence: 99%